Effect of Different Temperature in DNA State of Teeth Samples - Mona N. Al-Terehi (Journal of Global Pharma Technology, 2017)
There are many forensic  techniques used today that benefit to identify human remains from mass grave, explosion, fire, disasters, first step of DNA analysis was DAN extraction from biological evidence ,DNA retraction must be free from contamination as possible. The source of DNA is varying numerous as blood, saliva, nail, hair, bone, skin, urine and teeth. All source of DNA can be isolated from any living or dead organism even from ancient specimens. The aims of this study was evaluated DNA  states in teeth samples which exposure to heat at different time, Teeth sample were collected from 30 female from Q adisiyah province \ Iraq. Extraction of DNA were made by Gene MATREX UROX Bone DNA purification kit ,27teeth were burn at 100°C,500°C,1000°C  for(10,30,60) minutes,3 sample of teeth were extraction without exposure to heat as control. The results show that genomic DNA was obtained only in samples exposure to 100°Cand 500°C, no DNA was obtained from samples at 1000°C. The amplification of Exon -7 of gene CYP1A1 by PCR show that 20% of samples was amplified in the 100 C and 500 C grope and no amplification appeared in 1000 C samples. We concluded that DNA was more stable in teeth sample under different temperature, furthermore sample under 1000 C need more investigation like RT-PCR to detect DNA state in low concentrations and purity.Keywords: DNA states, Forensic evidence, Teeth samples PCR.